PENGEMBANGAN MODUL MATEMATIKA YANG TERINTEGRASI TEKNOLOGI QUICK RESPONSE CODE PADA MATERI PERSAMAAN GARIS LURUS KELAS VIII SMP - Wiko Alsepriadi (Jurnal Edukasi dan Penelitian Matematika, 2022)
The purpose of this research is to develop a Mathematics Module with Quick Response Code Technology on Linear Equations that is valid and practical to support the success of the mathematics learning process for class VIII SMP/MTs. This module uses the Plomp development model which consists of 3 stages, namely the preliminary research, the development or prototyping and the assessment. The subjects of this research were 12 students grade VIII of SMPN 6 SOLSEL. The instruments used are validity sheets and practicality sheets .The mathematics module is valid with 83.81% results in the valid category. Practicality based on student response questionnaires. The results of the questionnaire obtained a practical value of 80.43% with a practical category. Thrus, it can be said that the Mathematics Module with Quick Response Code Technology on Line Equation Material for Class VIII SMP/MTs that has been produced can be declared valid and practical. Keywords – Development, Linear equation ,Module, Quick Response Code